Odontogenic myxofibroma- Report of a rare entity (Journal of Pathology of Nepal, 2016)
Odontogenic myxofibroma is a rare, benign tumor, which is considered to be the variant of odontogenic myxoma. It is locally infiltrative, aggressive and has high recurrence rate. Only 24 specific cases of myxofibroma have been reported since 1950 and only two cases have been reported with excessive calcifications till 2012. Here, we report a rare case of Odontogenic myxofibroma with calcifications in 53 years old female patient who presented with the chief complain of swelling. The final diagnosis of Odontogenic myxofibroma was established after histopathological and immunohistochemical examination.